Respuesta :

-1x+5y+4z=48
4x-3y+6z=18
6x-2y+5z=0
multiply the first equation by 4 and add the results to the second equation:
-1x+5y+4z=48
17y+22z=210
6x-2y+5z=0
multiply the first equation by 6 and add the results to the third equation:
-1x+5y+4z=48
17y+22z=210
28y+29z=288
multiply the second equation by -28/17 and add the result to the third equation:
-1x+5y+4z=48
17y+22z=210
-123/17z=-984/17
solve for z
-123/17z=-984/17
z=8
then solve for y
17y+22z=210
17y+22*8=210
y=2
solve for x substituting y=2 and z=8 into the first equation:
4x-3(2)+6(8)=18
x=-6
so the solutions are x=-6, y=2, z=8